Perlindungan Hak Narapidana dalam Peradilan Pidana di Indonesia - Nur Faidah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The problems in this research are: 1) Why are the regulations for protecting the rights of prisoners in the criminal justice system in Indonesia not based on the value of justice, 2) What are the weaknesses in the regulations protecting the rights of prisoners in the current criminal justice system. The research method uses the constructivism paradigm, with an empirical juridical approach, and a descriptive research type. Types and sources of data using secondary materials in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Methods of data collection using literature, and qualitative analysis methods. The results of the study are: 1) Regulations for the protection of convicts' rights in the criminal justice system in Indonesia are not based on the value of justice; 2) Weaknesses in the regulation on the protection of convicts' rights in the current criminal justice system from the aspects of legal substance, legal structure and legal culture.